The power of small-scale solar: gender, energy poverty, and entrepreneurship in Tanzania. Issue 1 (2nd January 2019) - Gray, Leslie; Boyle, Alaina; Francks, Erika; Yu, Victoria
ABSTRACT: Energy poverty is a major challenge in the developing world, with an estimated 1.2 billion people lacking household electricity. Although energy poverty affects both men and women, the burden of household energy supply disproportionately affects women in low-income countries in the developing world. This article examines the impact of a women-oriented solar lighting social enterprise, Solar Sister, in Tanzania for both solar entrepreneurs and customers, demonstrating that solar lanterns positively impact household savings, health, education and women's economic productivity and empowerment. Our study argues that Solar Sister's approach is successful because of its explicit gender lens. Providing energy access to women translates to a pro-woman, pro-child, and pro-family development intervention.